Peranan Koperasi Simpan Pinjam Jaya Maju Sejahtera dalam Upaya Pengembangan UMKM di Kabupaten Way Kanan Lampung - Frillia Degustia; Ahmad Agus Saputra; Ricky Pebriansah; Intan Safitri; Yoga Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an economic sector that plays a vital role in driving economic growth, job creation, and equitable distribution of income. MSMEs are generally managed by individuals or small groups with limited business scale and relatively small capital. In their operations, MSMEs often face obstacles, particularly in terms of access to capital, business management, and product development. This study aims to determine the extent of the role of the Jaya Maju Sejahtera Savings and Loans Cooperative in supporting MSME development in Way Kanan Regency, as well as to identify factors that support and hinder this process. The research findings reveal that KSP Jaya Maju Sejahtera provides multidimensional contributions: (1) Providing access to financing through a microcredit scheme with a ceiling of IDR 5-50 million and competitive interest rates (8-12% per year); (2) Routine business development programs such as financial administration and marketing management training; (3) Business networking among cooperative members. Between 2021 and 2023, the cooperative successfully disbursed loans worth IDR 3.2 billion to 125 MSMEs, with a repayment rate of 92%. The main supporting factors include: (1) High level of trust between cooperative members; (2) Flexibility of credit requirements; (3) Intensive mentoring by cooperative administrators. Meanwhile, obstacles include: (1) Financial literacy of 62% of MSMEs is still in the low category; (2) Dependence on technology in 85% of MSMEs; (3) Limited access to modern markets. The research method used is a descriptive qualitative approach with data collection techniques through observation and interviews with cooperatives and MSMEs. The results of the study show that cooperatives have a large contribution in helping MSME financing through credit distribution which continues to increase. In addition, cooperatives also provide education and coaching to their members to increase business capacity.